The Influence of Infrastructure Development, Local Community Engagement, and Digital Promotion on Economic Welfare in Kudus - Aulia, Cholivatul; Sukardi, Agung Slamet (UIR Press, 2026)
This study investigates the determinants of regional economic welfare across eight strategic tourism destinations in Kudus Regency, focusing on the interplay between physical infrastructure, local community participation, and digital promotion. Using a quantitative approach, economic welfare is operationally defined through indicators of household income, MSME profits, job opportunities, and productive asset accumulation. Data were collected via stratified random sampling from 100 integrated respondents, including local residents, MSME players, and tourists, to validate economic impact from both supply and demand perspectives. Multiple linear regression analysis conducted through EViews 8 reveals that infrastructure development (X_1) yields no significant impact on economic welfare (p=0.190), suggesting a saturation point in physical facilities. Conversely, community participation (X_2) shows a significant yet negative correlation (p=0.011), indicating a